'That Medieval Eastern-European Shtetl Family of Yours': Negotiating Jewishness in Aline Kominsky Crumb's Need More Love (2007). Issue 2 (1st December 2015) - Precup, Mihaela
This article focuses on several representations of Jewishness from American underground cartoonist Aline Kominsky Crumb's memoir Need More Love (2007) and several more recent publications. In her work, Kominsky Crumb makes repeated references to almost every stereotypical aspect of the Jewish American middle-class community in which she was raised, from the accent to the clothes, social mannerisms, and even preferred type of plastic surgery. In conversation with Federica Clementi, Riv Ellen-Prell, and others, I read the comics collected in Need More Love in conjunction with several of the author's photographs in order to revisit the debate on the dynamic between comics and photography as modes of self-representation. I argue that, by narrowing down the potential of comics to what the medium can do as caricature, Kominsky Crumb connects to a long tradition of social satire and self-disparaging humour. However, by including photographs of herself in her work, she not only pays tribute to the more traditional norms of life-writing, but also invites an interpretation of her cartoon self as a masquerade of Jewish femininity staged upon a body whose vulnerability complicates the binary logic of the stereotype.